Efektivitas Salep Minyak Jintan Hitam (Nigella sativa) sebagai Antibakteri terhadap Staphylococcus aureus dan Pseudomonas aeruginosa - Arifullah, Muhamad Aqsal; Rukaya, Benazir Evita; Syuhada, Syuhada (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to evaluate the effectiveness of black cumin oil ointment as an antibacterial agent against Staphylococcus aureus and Pseudomonas aeruginosa. The ointment was formulated with three variations of black cumin oil concentrations (0.1%, 1%, and 10%) using a lipophilic base. The physical stability test was conducted by evaluating organoleptic properties, homogeneity, pH, spreadability, and adhesion. The antibacterial activity was tested using the well-diffusion method against Staphylococcus aureus and Pseudomonas aeruginosa and analyzed using the One Way ANOVA method followed by a post hoc Tukey test. The results of this study indicate that (1) The black cumin oil ointment demonstrated good physical stability, particularly in terms of homogeneity and pH; (2) The antibacterial activity test showed that the ointment with a 10% black cumin oil concentration (F3) effectively inhibited the growth of Staphylococcus aureus with an efficacy not significantly different from gentamicin ointment (p = 0.477), but significantly different from the negative control (p = 0.027). However, no antibacterial activity was observed against Pseudomonas aeruginosa.Conclusion: The 10% black cumin oil ointment formulation has the potential as a natural antibacterial agent against Staphylococcus aureus. These findings suggest that black cumin oil can be further developed as a natural-based topical therapy alternative for treating skin infections caused by Gram-positive bacteria.